A Study of Security Issues in Cloud Computing on Data Storage (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Cloud computing is a revolutionary mechanism that changing way to enterprise hardware and software design and procurements. Because of cloud simplicity everyone is moving data and application software to cloud data centers. The Cloud service provider (CSP) should ensure integrity, availability, privacy and confidentiality but CSP is not providing reliable data services to customer and to stored customer data. This study identifies the issues related to the cloud data storage such as data breaches, data theft, and unavailability of cloud data. Finally, we are providing possible solutions to respective issues in cloud.